Mathematical Problem Solving Profiles Of Students Viewed From Adversity Quotient (Aq) In The Class X Sman 14 Bulukumba - Hamzah Upu; Mayong Maman; Asdar Asdar; Desi Rukmana Fatma (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2019)
The research was descriptive research with qualitative approach which aimed to describe mathematical problem solving of profiles students viewed from Adversity Quotient (AQ). The instrument of the research was the researcher herself as the main instrument guided by AQ questionnaire, mathematical problem solving test, interview guideline, and field notes. The subjects of the research were the students of class X MIPA 1 and X MIPA 2 SMAN 14 Bulukumba who consisted of 2 climber students, 2 camper students, and 2 quitter students. The data were collected through task analysis and interview. The results of the research reveal that: 1) the profiles of climber students’ mathematical problem solving are: a) at the stage of understanding the problems, climber students are able to interpret the problems by illustrating what they know in the form of pictures based on their understandings through writing, b) at the stage of devising a plan of problem solving, climber students are able to plan formulae which are used to answer the problems given, c) at the stage of carrying out the plan, climber students are able to do calculations through pre-planned formulae, d) at the stage of looking back the answers, climber students do not feel satisfied with the results they obtain before they recheck the answers by returning the obtained results into the known items of problems. 2) The profiles of camper students’ mathematical problem solving are: a) at the stage of understanding the problem, camper students are able to interpret the problems by illustrating what they know in the form of pictures based on their understandings through writing, b) at the stage of devising a plan of problem solving, camper students are able to plan formulae which are used to answer the problems, c) at the stage of carrying out the plan, camper students are able to answer the problems through pre-planned formulae, d) at the stage of looking back the answers, camper students feel satisfied with the results they obtain without having to recheck the answers. 3) The profiles of quitter students’ mathematical problem solving are